Immunotherapy-Induced Overlap Syndrome: Myositis, Myasthenia Gravis, and Myocarditis—A Case Series - Nikhil Aggarwal; Diletta Bianchini; Rosemeen Parkar; Jennifer Turner (Case Reports in Medicine)
Immune checkpoint inhibitors (ICI) are monoclonal antibodies that target immune checkpoint inhibitory receptors. They have revolutionised cancer treatment but can be associated with a wide range of adverse side effects. Rarely, they can be associated with the triad of myositis, myasthenia gravis, and myocarditis or overlap syndrome. Prompt recognition and early intervention are needed to treat these potentially life-threatening conditions. We report a case series of patients with ICI-related overlap syndrome, including the first with avelumab, and discuss the current management guidelines.